The Energy Potential of the Black Sea Region: the Problems and Prospects - P. A. Vysotsky (Проблемы постсоветского пространства)
The Black Sea shelf contains significant hydrocarbon resources. Over the past decades the Black Sea countries, supported by Western oil and gas companies, have been developing various plans for the extraction and export of hydrocarbon resources to fore In solving this task, they faced a number of challenges due to the difficult production conditions. In addition, the Black Sea region was not in the focus of attention of oil and gas companies, which produced resources in other regions of the world. Nevertheless, the Black Sea countries have developed national programs for the production of hydrocarbons on the Black Sea shelf and are considering various options for their export to foreign markets.